Significance of umbilical artery doppler velocimetry in the perinatal outcome of growth restricted fetuses - Thomas, Jyothi Susan; Malliga, A.; Sethurajan, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objectives of the study are to determine the relationship between the umbilical artery Doppler and perinatal outcome in growth restricted foetuses and to compare the outcome with those of normal foetuses. Methods: A prospective observational study in which subjects were divided into two groups, pregnancies affected with intrauterine growth restriction (IUGR) and pregnancies with normal fetuses. Both the groups were followed with Doppler velocimetry of umbilical artery after 28 weeks till delivery. The perinatal outcome of both the groups with normal and abnormal umbilical artery Doppler (reduced/ absent/ reversed end – diastolic flow) were analysed with Chi-square test and student t - test using SPSS software version 15.0. Results: Umbilical artery Doppler velocimetry showed significant abnormality in growth restricted foetuses in comparison to normal foetuses. There was significant increase in the delivery of IUGR foetuses <37 weeks gestation(p<0.05). There was a significant increase in operative deliveries in both the groups with abnormal umbilical artery Doppler. A significant rise in adverse perinatal outcomes, Apgar <7 at 5 min and low birth weight in IUGR foetuses in comparison to normal foetuses (p<0.05). Conclusions: There is a strict correlation between abnormal umbilical artery Doppler velocimetry and an increased incidence of perinatal complications in growth restricted foetuses compared to normal foetuses. Hence, umbilical artery Doppler velocimetry should be used in all patients with fetal growth restriction, to identify impending hypoxia, to optimise the time of delivery and to optimise the perinatal outcome in these patients.